2019
DOI: 10.1142/s021797921950053x
|View full text |Cite
|
Sign up to set email alerts
|

Delay-induced synchronization transition in a small-world neuronal network of FitzHugh–Nagumo neurons subjected to sine-Wiener bounded noise

Abstract: Noise and delay are ubiquitous in brain and they have significant effects on neuronal network synchronization and even brain functions. Based on a small-world neuronal network of delayed FitzHugh–Nagumo (FHN) neurons subjected to sine-Wiener (SW) bounded noise, the effects of delay and SW noise on synchronization and synchronization transition are numerically investigated by calculating a synchronization measure R and plotting spatiotemporal patterns. The phenomenon of delay-induced synchronization transition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In past research, researchers have investigated the interaction between neurons and their networks in different brain regions using techniques like neuroimaging systems [ 56 59 ] and used computational models to predict the complex dynamics of neurons [ 60 , 61 ] and showed that noise plays an important role in the dynamical functionality of the neurons and their networks [ 62 , 63 ]. The fundamentals of the noise and delay in the communication of neuronal networks are still ubiquitous but they have a very strong implication for the functionality of neurons and their networks and in general, the synchronized functionality of the brain [ 64 , 65 ]. The noise has a tremendous effect as amplification of the weak neuronal signal and therefore enhances the detection of useful information in the signal [ 64 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In past research, researchers have investigated the interaction between neurons and their networks in different brain regions using techniques like neuroimaging systems [ 56 59 ] and used computational models to predict the complex dynamics of neurons [ 60 , 61 ] and showed that noise plays an important role in the dynamical functionality of the neurons and their networks [ 62 , 63 ]. The fundamentals of the noise and delay in the communication of neuronal networks are still ubiquitous but they have a very strong implication for the functionality of neurons and their networks and in general, the synchronized functionality of the brain [ 64 , 65 ]. The noise has a tremendous effect as amplification of the weak neuronal signal and therefore enhances the detection of useful information in the signal [ 64 ].…”
Section: Introductionmentioning
confidence: 99%
“…The fundamentals of the noise and delay in the communication of neuronal networks are still ubiquitous but they have a very strong implication for the functionality of neurons and their networks and in general, the synchronized functionality of the brain [ 64 , 65 ]. The noise has a tremendous effect as amplification of the weak neuronal signal and therefore enhances the detection of useful information in the signal [ 64 ]. The addition of noise in such networks/systems has unveiled hidden facts such as the development of the stochastic methodology to understand respective resonance [ 66 ], noise sustained synchronization [ 67 ], vibrational resonance [ 68 , 69 ], chaotic resonance [ 70 ], and coherent-resonance [ 71 ] in nonlinear dynamical systems.…”
Section: Introductionmentioning
confidence: 99%
“…Mostly, the small-world network has been considered as the neuronal system since proposed by Watts and Strogatz in 1998 [36], [37]. In addition, studies have proven that the human brain cortex has small-world properties [12], [16], [33], [35], [38]. The small-world model provides a powerful tool to investigate the structures and dynamics of the human brain.…”
Section: Introductionmentioning
confidence: 99%
“…The small-world model provides a powerful tool to investigate the structures and dynamics of the human brain. A lot of work concerned the neuronal dynamics of small-world networks [16], [38], [39]. Qu and Wang have explored the synchronization and spatiotemporal behaviors of small-world neuronal networks based on different neuron models [13], [22], [33], [34].…”
Section: Introductionmentioning
confidence: 99%
“…Many networks are used to simulate computation. According to the random connection probability, there are regular networks, small world networks and random networks [41,42]. From the perspective of the network topology, the common rule networks have local (nearest neighbor), global (all-to-all), non-local connections [43,44].…”
Section: Introductionmentioning
confidence: 99%